Rice Farming with Application of Integrated Pest Management (IPM): Analysis of Social and Economic Sustainability (Case Study in Besur Village, Lamongan District) - Aminudin Afandhi (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2020)
Environmental degradation and pest attack against rice plants obstruct efforts to increase rice production in Indonesia. one attempt to overcome the problem by applying rice farm with Integrated Pest Management (IPM). This study aimed to examine the sensitivity level of social and economic attributes that were sustainable in rice farming with IPM application. This research was conducted in September and October 2018 Village Besur, Lamongan District. The data used in this research were secondary and primary data. Secondary data obtained from literature studies while primary data obtained by observation and survey of farmers and stakeholders. Furthermore, the data were analyzed with RAP-IPM (Rapid Appraisal for Integrated Pest Management) approach by applying the techniques of MDS (Multidimensional Scaling) using software Rapfish (Rapid Assessment Techniques for Fisheries). The results showed that the sensitivity level of social and economic attributes was sustainable in rice farming with the application of IPM in Besur Village. This implies that the application of IPM is the right solution to improve the sustainability of rice farming in Indonesia.